The clinical outcomes of extended resections in patients with IV stage gallbladder cancers: A retrospective study from a large tertiary center - Zhang, Kecheng; Liu, Hu; Zhao, Yongyang; Zhang, Baohua (Frontiers in Oncology, 2022)
Background and aim : The role of extended resections in patients with clinical stage IV A gallbladder cancer (GBC) remains unclear. This study retrospectively analyzed the clinical outcomes of patients who underwent extended resections for IV GBC. Methods:Patients who were diagnosed with IV stage GBCs and underwent extended resections in Eastern Hepatobiliary Surgery Hospital, Shanghai, China, were retrospectively included in our study. Extended resection was defined as a major hepatectomy (resection of ≥3 liver segments), a pancreatoduodenectomy, or both. The clinical outcomes (baseline characteristics, preoperative variables,intraoperative variables, pathological outcomes, and follow-up data ) were obtained and analyzed. The factors associated with major postoperative complications and long-term survival were analyzed by logistic regression analyses. Results: From January 2011 to June 2017, 74 patients were included in our study. There were 33 (44.6%) males and the median age was 62.5 years (interquartile range [IQR], 56.0-67.0 years). According to pathological specimens, the median tumor size was 7cm (IQR, 6-8cm), 73(98.6%) of them received R0 resection and 72 (97.2%) of them were IV A stage GBC. Three perioperative deaths (5.4%) occurred, and major postoperative complications occurred for 15 patients (20.3%). Among them, 61 patients (82.4%) experienced recurrence and 17 patients (23.0%) were still alive after a median follow-up period of 52 months. The disease free survival time was 9 months (95% confidence interval [CI],7.8-10.2 months) and the overall survival was 18.0 months (95% CI, 15.2-20.8 months). Longer hospital stay days [odds ratio,(OR)=1.979, 95%CI:1.038-1.193, P=0.003), initial symptoms with abdominal pain (OR=21.489, 95%CI=1.22-37.57, P=0.036) , more blood transfusion volume during hospitalization (OR=1.036, 95%CI:1.021-1.058, P=0.005), and intraoperative hemorrhage (OR=18.56, 95%C:3.54-47.65, P=0.001) were independently associated with postoperative complications. Moreover, locally recurrence (OR=1.65, 95%CI:1.17-1.96, P=0.015), and more adjuvant chemotherapy cycles (OR=1.46, 95%CI:1.13-1.76, P=0.026) were independently associated with long-term survival. Conclusion: Our retrospective study identified that extended resections can be safely and efficaciously performed on stage IV GBC patients in selected patients and performed by experienced surgeons.